Peranan Humas di Lembaga Pendidikan Al-Qur’an (Studi Desktiptif Kualitatif Rumah Tahfizh Qur’an Al Azhar Al Syarif Manarap Tengah Kabupaten Banjar) - Syahril Taufiq Hidayat; Jerina Fujiantie (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2023)
Abstract: This research aims to find out how the role of public relations in Qur'anic educational institutions in order to build communication relations between the Rumah Tahfizh Qur'an Al Azhar Al Syarif Qur'an and the public. This research is a descriptive qualitative approach. Data collection technique using participant observation, interviews, and documentation. The informants in this research are the Public Relations Coordinator, the Chief Director, the Head of Academic Affairs, the community, and the santri's parents in the surrounding environment of the Rumah Tahfizh Qur'an Al Azhar Al Syarif. The data analysis technique is interactive analysis with stages: data reduction, data presentation, and conclusion drawing. The results showed that the function of public relations at Rumah Tahfizh Qur'an Al Azhar Al Syarif is divided into 5 roles, which are: as an expert advisor, as a communication facilitator for the public, as a problem-solving process, building an image, and promoting Rumah Tahfizh Qur'an Al Azhar Al Syarif. The role of public relations has been running according to the standard operating procedures of the Rumah Tahfizh Qur'an Al Azhar Al Syarif. This is shown by the rapid development seen from the number of teachers and and students in a period of 5 years.